2004
DOI: 10.1002/app.20405
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical properties and biodegradability of green composites based on biodegradable polyesters and lyocell fabric

Abstract: Green composites composed of regenerated cellulose (lyocell) fabric and biodegradable polyesters [poly(3-hydroxybutyrate-co-3-hydroxyvarelate) (PHBV), poly(butylene succinate) (PBS), and poly(lactic acid) (PLA)] were prepared by compression-molding method. The tensile moduli and strength of all the biodegradable polyester/ lyocell composites increased with increasing fiber content. When the obtained PLA/lyocell composites were annealed at 100°C for 3 h, the tensile strength and moduli were lowered despite th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
69
0
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 138 publications
(75 citation statements)
references
References 15 publications
5
69
0
1
Order By: Relevance
“…The study observed that unidirectional biodegradable composites fabricated using an emulsion-type PLA resin and kenaf fibres at a fibre content of 70 wt.% had high tensile and flexural strengths of 223 MPa and 254 MPa respectively. Shibata et al [16] study prepared composites with PLA/lyocell fabric by compression moulding. The tensile modulus and strength of lyocell/PLA composites improved with increasing fibre content.…”
Section: Introductionmentioning
confidence: 99%
“…The study observed that unidirectional biodegradable composites fabricated using an emulsion-type PLA resin and kenaf fibres at a fibre content of 70 wt.% had high tensile and flexural strengths of 223 MPa and 254 MPa respectively. Shibata et al [16] study prepared composites with PLA/lyocell fabric by compression moulding. The tensile modulus and strength of lyocell/PLA composites improved with increasing fibre content.…”
Section: Introductionmentioning
confidence: 99%
“…Compósitos verdes constituídos de fibras de celulose e poliésteres biodegradáveis (poli(hidroxibutirato-co-valerato), poli(succinato de butileno) e poli(ácido lático)) foram preparados e caracterizados por Shibata e colaboradores 182 . Os módulos de tensão e a resistência mecânica de todos os compósitos preparados são maiores do que os dos polímeros puros.…”
Section: Biocompósitos: Fibras Lignocelulósicas E Polímeros Biodegradunclassified
“…In recent years, the utilization of plant fibers to reinforce polymers has drawn the attention of various researchers (Shibata et al 2004;Lee and Wang 2006;Li et al 2007;Ku et al 2011;Faruk et al 2014). Plant fibers, such as wood fibers, bamboo fibers, and jute, not only have great specific strength and a wide range of sources, but also are inexpensive, renewable, and biodegradable.…”
Section: Introductionmentioning
confidence: 99%